Chemistry and microbial sources of curdlan with potential application and safety regulations as prebiotic in food and health. (July 2020) - Verma, Deepak Kumar; Niamah, Alaa Kareem; Patel, Ami R.; Thakur, Mamta; Singh Sandhu, Kawaljit; Chávez-González, Mónica L.; Shah, Nihir; Noe Aguilar, Cristobal
Graphical abstract: Highlights: Chemical composition, sources and applications of curdlan for food are discussed. Curdlan is used as stabilizing, texturing, water holding, and viscosifying agent. Curdlan shows prebiotic potential indicating its value to develop functional foods. Huge variations have been observed about safety regulation of curdlan across globe. Curdlan can be a sustainable substitute for food additives in the coming years. Abstract: Curdlan – a homopolysaccharide is comprised of glucose using β-1, 3-glycosidic bond and produced by different types of microorganisms as exopolysaccharide. Curdlan gel is stable during freezing and thawing processes which find several applications in food and pharmaceutical industries. It acts as a prebiotic, stabilizer and water-holding, viscosifying and texturing agent. Additionally, curdlan gel is used as a food factor to develop the new products e.g. milk fat substitute, non-fat whipped cream, retorting (freeze-drying) process of Tofu, low-fat sausage, and low-fat hamburger. However, a great variation exists among different countries regarding the regulatory aspects of curdlan as food additives, dietary components or prebiotic substances. Therefore, the present review paper aims to discuss safety issues and the establishment of common guidelines and legislation globally, focusing on the use the applications of curdlan in the food sector including the development of noodles, meat-based products, and fat-free dairy products. This review analyzes and describes in detail the potential of curdlan as a sustainable alternative additive in health and food industries, emphasizing on the chemical composition, production, properties, and potential applications.